Exploring The Mediating Role of Digital Literacy In The Relationship Between Islamic Education And Youth Political Participation: Evidence From Pakistan - Ahmed, Rizwan (Al-madinah: Journal of Islamic Civilization, 2025)
This study establishes the role of digital literacy in explaining the connection between Islamic primary education and the current role of Pakistani youth in the political process. In the age when more and more of the political processes take place online, it is crucial to comprehend how religious learning and digital skills converse to create youth interest in the democratic processes. The research information was derived through self-administered structured questionnaire among 250 youngsters in urban centers of Pakistan as a result of which 198 workable responses were obtained. The mediation analysis conducted with the method of regression indicated that Islamic education has a considerable positive effect on youth political participation, and one of the mediators of this association is digital literacy. The results show that the youths who have developed greater COMPETENCE with regard to the process of Islamic education are more politically convened once empowered with digital know-how they would consider participating in online civil discourses and to gain exposure to a varied range of views. Indeed, the study convinces the educational policymakers, specifically those who handle the educational institutions that are under the banner of Islam to inculcate the aspects of digital literacy development in educational programs so as to raise informed and engaged citizens. Contribution to larger debate Modernization is a process that implies the increase of active and active citizens in urban settings across the world, and more specifically the involvement of religion and technology in everyday life is a topic that can be discussed, and this work helps to do so.